Synthesis and antibacterial activity of novel 2-(arylimino)thiazolidin-4-one and 2-(benzylidenehydrazono)-3-arylthiazolidin-4-one derivatives - Ebaa M. El-Hossary, Yassin M. Nissan, Katharina Edkins, Heike Bruhn (Journal of Applied Pharmaceutical Science, 2016)
The ongoing spread of multidrug-resistant bacteria demands an intensive search for new antibacterial agents. In the present study, a series of new 1,3-thiazolidin-4-ones has been synthesized and investigated for its in vitro antibacterial activity. The most potent antibacterial compound 4c was found to be active, at low micromolar range, against Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis and the pneumonic plague causative agent Yersinia pestis with minimum inhibitory concentrations of 5 µM, 2.5 µM, 2.5 µM and 5 µM, respectively. Compound 4c showed the ability to kill E. faecalis JH212 strain with a minimum bactericidal concentration of 5 µM. Furthermore, compounds 9b and 10a inhibited the biofilm formation in S. epidermidis, where they showed 70% to 80% inhibition at a concentration of 40 µM.
Keywords: 1,3-Thiazolidin-4-oneAntibacterial activityMinimum inhibitory concentration Minimum bactericidal concentrationBiofilm formation.